Brain energy rescue: an emerging therapeutic concept for neurodegenerative disorders of ageing - Cunnane, Stephen C.; Trushina, Eugenia; Morland, Cecilie; Prigione, Alessandro; Casadesus, Gemma; Andrews, Zane B.; Beal, M. Flint; Bergersen, Linda H.; Brinton, Roberta D.; de la Monte, Suzanne; Eckert, Anne; Harvey, Jenni; et al. (Nature reviews. Drug discovery, 2020)
The brain requires a continuous supply of energy in the form of ATP, most of which is produced from glucose by oxidative phosphorylation in mitochondria, complemented by aerobic glycolysis in the cytoplasm. When glucose levels are limited, ketone bodies generated in the liver and lactate derived from exercising skeletal muscle can also become important energy substrates for the brain. In neurodegenerative disorders of ageing, brain glucose metabolism deteriorates in a progressive, region-specific and disease-specific manner - a problem that is best characterized in Alzheimer disease, where it begins presymptomatically. This Review discusses the status and prospects of therapeutic strategies for countering neurodegenerative disorders of ageing by improving, preserving or rescuing brain energetics. The approaches described include restoring oxidative phosphorylation and glycolysis, increasing insulin sensitivity, correcting mitochondrial dysfunction, ketone-based interventions, acting via hormones that modulate cerebral energetics, RNA therapeutics and complementary multimodal lifestyle changes.